1996
DOI: 10.1093/oxfordjournals.ndt.a027207
|View full text |Cite
|
Sign up to set email alerts
|

Late diagnosis of chronic renal failure and mortality on maintenance dialysis

Abstract: Patients with a late diagnosis have a higher mortality risk during the first 6 months of maintenance dialysis. This increased risk is related to comorbid conditions, some of which could be prevented by predialysis care. Interventions to promote early diagnosis of CRF and adequate predialysis follow-up need to be evaluated if the survival of patients with chronic renal failure is to improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(107 citation statements)
references
References 5 publications
4
94
1
8
Order By: Relevance
“…The findings of the present study differ from those of previous observational cohort studies, which suggested that early dialysis commencement was associated with important clinical benefits (21)(22)(23)(24)(25)(26)(27)(28). For example, in the CANUSA study (29), the 2-year survival of PD patients with a measured weekly GFR of at least 38 L (average of urinary urea and creatinine clearances) at dialysis commencement was significantly superior to that of PD patients with a measured weekly GFR of less than 38 L (82.1% vs 73.6%, p = 0.01).…”
Section: Johnson Et Alcontrasting
confidence: 99%
“…The findings of the present study differ from those of previous observational cohort studies, which suggested that early dialysis commencement was associated with important clinical benefits (21)(22)(23)(24)(25)(26)(27)(28). For example, in the CANUSA study (29), the 2-year survival of PD patients with a measured weekly GFR of at least 38 L (average of urinary urea and creatinine clearances) at dialysis commencement was significantly superior to that of PD patients with a measured weekly GFR of less than 38 L (82.1% vs 73.6%, p = 0.01).…”
Section: Johnson Et Alcontrasting
confidence: 99%
“…It has been reported that residual renal function and serum albumin are both important predictors for patient survival (26)(27)(28)(29)(30). On the other hand, our urgentstart patients were also younger, and so the risk of death was partly offset.…”
Section: Discussionmentioning
confidence: 80%
“…Data from multiple international studies have shown that delayed referral to a nephrologist is a significant problem and is associated with a higher prevalence of uremic complications at the initiation of dialysis, with increased hospitalization and higher cost of care. [21][22][23][24] In addition, Arora and colleagues demonstrated that incident dialysis patients who were referred late (defined as the first encounter with a nephrologist occurring within 4 months of dialysis initiation) were significantly more likely to have hypoalbuminemia and hypocalcemia and less likely to have received EPO and a permanent vascular access before the first hemodialysis. Late referrals to a nephrologist were also associated with lower levels of renal function at dialysis initiation, as documented by higher serum creatinine and a higher proportion of patients with predicted glomerular filtration rate <5 mL/min per 1.73 m 2 .…”
Section: O R I G I N a L R E S E A R C Hmentioning
confidence: 99%